The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/978-1-4615-0487-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Synthesis Methods for MEMS

Abstract: of the hardcover 1st edition 2003 AU rights reserved. No part of this publication may be reproduced, stored in a retrieval system or transmitted in any form or by any means, electronic, mechanical, photo-copying, microfilming, recording, or otherwise, without the prior written permission of the publisher, with the exception of any material supplied specifically for the purpose of being entered and executed on a computer system, for exclusive use by the purchaser of the work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…The design of compliant structures is an area of significant interest in the MEMS community, and there are methods to optimize the shape of flexures for mechanical or geometric advantage, or for a desired motion path [152], [153].…”
Section: Flexural Suspensionsmentioning
confidence: 99%
“…The design of compliant structures is an area of significant interest in the MEMS community, and there are methods to optimize the shape of flexures for mechanical or geometric advantage, or for a desired motion path [152], [153].…”
Section: Flexural Suspensionsmentioning
confidence: 99%
“…These methods were successfully applied to the synthesis of micro-compliant mechanisms [45] [47]. A complete review of automated synthesis methods for MEM devices can be found in [46].…”
Section: A Automated Synthesis Of Mem Devicesmentioning
confidence: 99%
“…Even though topology optimization-based synthesis methods have been reported for a variety of actuations in microsystems [3], such an attempt for electrostatically actuated microstructures is reported only recently [4]. The inability to smoothly interpolate the state of the material from a conductor to a dielectric or a void was perhaps a reason for this.…”
Section: Background and Motivationmentioning
confidence: 99%